Vzdělávání žáků s Aspergerovým syndromem v inkluzivní třídě Metodická příručka - Bazalová, Barbora (Masaryk University Press, 2020)
Title in English: Education of Students with Asperger Syndrome in the Inclusive Classroom. The methodological guide focuses on developing social, emotional, and communication skills of students with Asperger syndrome and their classmates, teachers, assistant teachers, and the school staff. We aim to extend knowledge on the specific approaches to students with AS in the inclusive classroom. We offer coping strategies in situations arising from the interaction between the school actors. A classroom adaptation and fostering positive relationships between classmates are the critical factors for positive school experiences of everybody. We present specific cases from the participatory classroom observation. Furthermore, we discuss the difficulties in the inclusive classroom and offer incentives to prevent these situations. We provide the readers with the specific activities for the groups with the students with AS.